Dark fingernails - Vaani Valerie Visuvanathan; Koh Kwee Choy (Malaysian Family Physician, 2015)
Madam S, a 40-year-old woman of South Asian origin was diagnosed with HIV infection through spousal contact tracing. Her husband, who had a history of intravenous drug use, was diagnosed with HIV infection while incarcerated in a prison. She was asymptomatic and had no clinical evidence of opportunistic infections. Her CD4 cell count was 180 cells/mm3 . Based on the Malaysian national guidelines for the treatment of adults with HIV-infection, Madam S was commenced on cotrimoxazole (Bactrim) tablets for prophylaxis against Pneumocystis jiroveci infection and a combination of antiretroviral (ARV) agents consisting of zidovudine (AZT), lamivudine (3TC) and efavirenz (EFV) to treat her HIV infection. After 3 months, Madam S returned for the follow-up at the infectious diseases clinic. She was tolerating her ARV regime well with minimal side effects. She complained of fingernail colour changes (Figures 1 and 2), which were aesthetically distressing to her. Almost all her fingernails were noted to have longitudinal bands of hyperpigmentation. However, her toenails were spared and there was no hyperpigmentation of mucosa membranes and palmar creases.